2016
DOI: 10.3892/etm.2016.3924
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a small dose of aspirin on quantitative test of 24-h urinary protein in patients with hypertension in pregnancy

Abstract: The aim of the present study was to determine the effect of a small dose of aspirin on a quantitative test of 24-h urinary protein in patients with hypertension in pregnancy. In total, 224 patients with hypertension in pregnancy were continuously selected and were randomly divided into the control group (50 cases with conventional therapy), aspirin 50 mg/day group (60 cases), aspirin 75 mg/day group (58 cases), and aspirin 100 mg/day group (56 cases). Clinical effects were compared from 16 gestational weeks to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…Four studies reported as an outcome, emergency CS for intrapartum fetal distress, of which three showed a non‐significant increase in risk, and one demonstrated a non‐significant risk reduction in women taking LDA. Birth asphyxia/acidosis was reported in five studies, however, in one study it was defined as either cord artery pH < 7.15 or base excess < −7 mmol/L or 5‐min Apgar score < 6, in another as base excess > 90 th centile (12 mEq/L) and in a third as cord pH < 7.15, while it was not defined in the other two studies. Three of the studies showed a non‐significant increase whilst the remaining two showed a non‐significant reduction in the risk of birth asphyxia/acidosis in women receiving LDA.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies reported as an outcome, emergency CS for intrapartum fetal distress, of which three showed a non‐significant increase in risk, and one demonstrated a non‐significant risk reduction in women taking LDA. Birth asphyxia/acidosis was reported in five studies, however, in one study it was defined as either cord artery pH < 7.15 or base excess < −7 mmol/L or 5‐min Apgar score < 6, in another as base excess > 90 th centile (12 mEq/L) and in a third as cord pH < 7.15, while it was not defined in the other two studies. Three of the studies showed a non‐significant increase whilst the remaining two showed a non‐significant reduction in the risk of birth asphyxia/acidosis in women receiving LDA.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies in which LDA was started ≤ 16 weeks' gestation reported placental abruption as an outcome. The meta‐analysis demonstrated that LDA was not associated with an increased risk of placental abruption (RR, 0.68; 95% CI, 0.40–1.15; P = 0.15) and this effect was independent of the aspirin dose used.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations